1922
DOI: 10.1084/jem.36.5.559
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Oxygen Content of Cutaneous Blood (So Called Capillary Blood)

Abstract: 1. A procedure is devised whereby cutaneous blood (so called capillary blood) from a finger-tip can be obtained for gas analyses without coming in contact with the air. 2. Determination was made of the oxygen content of the arterial, cutaneous, and venous blood respectively from a normal resting individual, the arterial and cutaneous blood showing the same oxygen content (97.5 and 96.6 per cent of the total oxygen-combining power of the blood). Venous blood drawn simultaneously was 75 per cent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1925
1925
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…Lundsgaard and Moller (25) found that the blood obtained by cutaneous incision is identical in oxygen content with arterial blood. We have therefore used cutaneous blood obtained by a clean deep prick with a sharp needle.…”
Section: Methodsmentioning
confidence: 95%
“…Lundsgaard and Moller (25) found that the blood obtained by cutaneous incision is identical in oxygen content with arterial blood. We have therefore used cutaneous blood obtained by a clean deep prick with a sharp needle.…”
Section: Methodsmentioning
confidence: 95%
“…Alternative techniques to arterial sampling have been investigated in both humans (Lundsgaard & Moller 1922; Singer et al. 1955; Maas & van Heijst 1961; Langlands & Wallace 1965; Harrison et al.…”
Section: Introductionmentioning
confidence: 99%
“…It was first suggested by Hagedorn (1920) that capillary blood was equivalent to arterial blood in sugar content, and Lundsgaard and Moller (1922) concluded from their observations on capillary and arterial blood oxygen concentrations that cutaneous blood should have the same sugar content as arterial blood. Since then it has been confirmed in the adult that capillary blood sugar concentration approximates to arterial blood sugar concentration (Foster, 1923;Langner and Fies, 1942;Somogyi, 1948), and studies on arteriovenous blood sugar concentration differences have been based on this assumption (Russell and Bruce, 1964).…”
Section: Discussionmentioning
confidence: 99%